A practical approach used to plan and execute, quantify and qualify an effective well clean-up strategy. Issue 1 (1st December 2019) - Woods, Robert; Bothwell, Thomas; Birt, Benjamin; Hopper, Tim; Higginson, Simon
Summary: Bringing a new well on-line is an expensive proposition and the need to ensure optimal performance is critical. Saturation and contamination of the drilling fluid with fines and subsequent invasion of the formation has historically resulted in hundreds of hours per well of invisible lost time during the clean-up phase of the well. New technologies, workflows and methods that can reduce costs/turnaround on projects were conducted on a large multi-well project in Perth, Western Australia, to maximise well efficiencies. Data from multiple sources were used to optimise and validate well clean-up operations with the aim to maximising production. This case study uses integration of well testing transient pressure data, Borehole Magnetic Resonance (BMR) derived transmissivity and flow logging to quantify success of clean-up/development of water wells, to reduce cost and optimise productivity. This case study demonstrates the successful implementation of an integrated approach to well clean-up using several scales of permeability data from core to wireline BMR to well test. This case study demonstrates that, in this particular setting, the use of the presented methodology was cost effective, yielded positive confirmation of asset delivery, and has led to a 90% reduction in clean-up associated time.